Analisis Penetapan Harga Beras dan Minyak Goreng oleh Pemerintah Berdasarkan Pemikiran Ibnu Khaldun - Abelia Sukma; Rika Widianita (Lembaga Yasin AlSys, 2026)
This research problem arises from the importance of understanding Ibn Khaldun’s thought on price and its relevance to the current price-setting policies of the Indonesian government. This study aims to analyze the conformity of government pricing policies with Ibn Khaldun’s thought and to identify their impact on economic stability and public welfare. This study employed a qualitative method with a library research approach. The data used were secondary data derived from books, journals, scientific articles, research reports, and relevant classical literature. Data collection was carried out through the stages of topic identification, searching, selection, reading, and literature analysis, while data analysis was conducted using thematic analysis and content analysis to interpret the data systematically. The results show that the Indonesian government’s pricing policy is indirect and corrective in nature, so that it does not eliminate the market mechanism. This policy is in line with Ibn Khaldun’s thought, which emphasizes the importance of the state’s role in maintaining economic balance, protecting society, and creating justice without restricting the freedom of economic activity. These findings affirm that government intervention in price-setting can be understood as an effort to maintain economic stability and public welfare while remaining within the framework of economic justice.